(untitled) (Journal of Comparative & International Higher Education, 2024)
Preparing English as a Foreign Language (EFL) teachers is a key challenge for higher education institutions in countries like Ecuador. This research summary describes the language use practices that university-based English language teacher educators employ when teaching content courses (such as pedagogy and research methods) and explores how these relate to their expressed purposes of teacher education and language ideologies. The convergent mixed-methods design employs survey data from 115 professors from 21 Ecuadorian universities and focus group data from 28 of those professors with various language use approaches. This research is guided by decolonial theory and the Capabilities Approach and by literature on linguistic imperialism, native-speakerism, and multilingualism. Findings extend research on language use from the English teaching field into teacher education and Comparative and International Higher Education research, where exploration of the benefits and drawbacks of English-only versus multilingual approaches are needed given the prevalence of English-medium instruction.